Regional detection and reconstruction of unknown internal or boundary sources - Afifi, Larbi; El Jai, Abdelahaq; Merry, Malika (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this paper is to study the problem of regional detection, to characterize internal or boundary regionally detectable sources and regionally spy sensors, and to establish a relationship between these sensors and regionally strategic sensors. It is shown how to reconstruct a regionally detectable internal or a boundary source from a given output, with an extension to the case when the output is affected by an observation error. Numerical results are given in the case of a diffusion system.
Keywords: sources; detection; observation; region; sensors